Peran Tanggung Jawab Sosial Perusahaan dan Ukuran Perusahaan Terhadap Penghindaran Pajak - Khalisa Fahira; Nera Marinda Machdar (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
This study aims to examine the existing literature on the relationship between Corporate Social Responsibility (CSR), company size, and tax avoidance. CSR encompasses ethical business practices adopted by companies, including their compliance with tax regulations. In contrast, larger companies often have more resources and broader networks, which enable them to implement more effective tax avoidance strategies. The research methodology involves a comprehensive literature review, which includes the development of a theoretical framework, identifying relevant variables, and analyzing findings from previous studies. The main objective is to investigate how CSR and company size influence tax avoidance. The results show significant differences in the interaction between CSR, company size, and tax avoidance, highlighting inconsistencies in previous research findings. Thus, this study provides a deeper understanding of the current dynamics surrounding these issues.